Pathogenicity and symptomatology of Apoharknessia eucalyptorum on leaves and stems of Eucalyptus and Corymbia - de Almeida Garrett, Alexandre Techy; Figueiredo Filho, Afonso; Imani, Jafargholi; dos Santos, Álvaro Figueredo; Tambarussi, Evandro Vagner [UNESP]; de Camargo, Mariane Bueno; de Oliveira Garcia, Flávio Augusto; Kogel, Karl-Heinz (Springer Nature, 2024)
Apoharknessia eucalyptoru m is associated with leaf spots on Eucalyptus dunnii in Southern Brazil; however, no data about its symptoms and severity are currently available. In this study, inoculation, symptomatology, and severity on leaves and stems of E. dunnii and leaves of Corymbia citriodora are analyzed and discussed. Detached and intact seedling leaves and seedling stems, with and without wounds, were inoculated with A. eucalyptorum. The severity of leaves was assessed based on the lesion area, whereas the severity on stems was considered by the size of the lesions. After inoculation, the following symptoms were observed on leaves with and without lesions: brown, circular or irregular lesions, occurring along the leaf margins, sparsely distributed, or coalescing throughout the leaf blade. The severity on detached leaves ranged from 13 to 63 % on E. dunnii and from 30 to 38 % on C. citriodora, whereas on intact seedling leaves the severity was observed only on wounded tissues, with 11.90 % on E. dunnii and 19.63 % on C. citriodora. Only inoculated stems of E. dunnii with wounds showed signs of the pathogen. This study confirms the pathogenicity of A. eucalyptorum on both E. dunnii and C. citriodora, a new host for the disease, and concludes that although the pathogen can be considered a primary pathogen based on detached leaf inoculations, the infection on non-wounded tissues is limited. Thus, the distribution of A. eucalyptorum and the possible impacts of the pathogen on Eucalyptus spp. plantations should be monitored.
Keywords: Inoculation; Leaf blight; Leaf spot; Stem canker; Symptomatology